Crystallizer casting powder for medium carbon steel and preparation method thereof
Through the chemical composition and modification process of specific ratios, a crystallizer for medium-carbon steel with suitable viscosity was prepared, which solved the problem of inappropriate viscosity of the protection slag in the prior art, and achieved improvement in the quality of the casting billet and continuous casting Stability of the process.
Patent Information
- Application Number
- CN202411625735.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
The existing crystallizers for medium-carbon steel protective slag have problems with inappropriate viscosity during casting, resulting in quality defects in the casting billet, such as corner cracks, narrow edge bulges and corner cross cracks.
Chemical components with specific ratios include wollastonite, magnesium slag, quartz, bentonite, coke gemstone, fluorite, soda ash, manganese carbonate, boron glass powder, magnesium sand powder, modified carbon materials and modified binders , through ball milling, ultrasonic treatment and spray granulation, crystallizer protective slag with suitable melting speed and viscosity was prepared.
It ensures uniform consumption of the thickness of the liquid slag layer, ensures smooth progress of the continuous casting process, avoids the quality defects of medium-carbon steel casting billets, and improves the overall quality of the casting billets.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of protective slag, and in particular relates to a crystallizer protective slag for medium carbon steel and a preparation method thereof. Background Art
[0002] With the rapid development of the steel industry, the requirements for the quality of steel products are increasing, especially for medium carbon steel, which is widely used in machinery manufacturing, automobile industry and other fields. Mold protection slag is very important in the continuous casting process of steel. It not only plays a role in heat insulation and prevents oxidation of molten steel, but also effectively controls heat transfer and lubricates the ingot, thus ensuring the smooth progress of the continuous casting process and improving the quality of the ingot.
[0003] With the development of continuous casting technology, the performance requirements for protection slag are becoming higher and higher, especially when casting medium-carbon steel with high hydrogen content. The selection and performance of protection slag have a decisive influence on the stability of the continuous casting process and the quality of the ingot. In particular, the basicity, melting characteristics, lubrication properties and viscosity of the protection slag have a greater impact on the continuous casting process. Therefore, the chemical composition of the protection slag needs to be finely controlled and modified according to the specific continuous casting conditions.
[0004] Chinese patent CN 116274906 A discloses a mold protection slag for casting high hydrogen content medium carbon steel molten steel and its application, the chemical composition of the mold protection slag is as follows: SiO 2 :25-32%, CaO: 29-36%, Al 2 O 3 : 1-4%, MgO: 3-6%, Na 2 O: 7-12%, F - : 6-10%, C 总 :3-6%, MnO:2-4%, Li 2 O: 0.5-1%, and the rest are other inevitable impurities. Using this crystallizer protection slag to cast medium-carbon steel with high hydrogen content can significantly reduce the incidence of emergency speed reduction due to crystallizer sticking alarm and steel leakage during continuous casting; however, the protection slag does not contain additives such as binder and water reducer, which affects the viscosity of the formed protection slag and will cause defects in the quality of the casting to a certain extent.
[0005] Therefore, it is urgent to develop a mold protection slag for medium carbon steel with appropriate viscosity and good casting quality. Summary of the invention
[0006] In view of the existing technical problems, the purpose of the present invention is to provide a mold powder for medium carbon steel and a preparation method thereof. The mold powder of the present invention has a reasonable proportion of chemical components, a suitable melting rate and viscosity, effectively ensures the thickness of the liquid slag layer, and enables the powder to be consumed evenly, thereby ensuring the smooth progress of the continuous casting process and avoiding quality defects such as corner cracks, narrow edge bulging, and transverse cracks at the corners of the medium carbon steel ingot.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] On the one hand, the present invention provides a crystallizer protective slag for medium carbon steel. The crystallizer protective slag comprises the following raw materials, measured by weight: 20-40 parts of wollastonite, 20-40 parts of magnesium slag, 2-6 parts of quartz, 1-5 parts of bentonite, 2-6 parts of pyroxene, 3-10 parts of fluorite, 1-3 parts of soda ash, 1-2 parts of manganese carbonate, 3-7 parts of borosilicate glass powder, 2-4 parts of magnesia powder, 6-10 parts of carbonaceous material, and 2-4 parts of modified binder.
[0009] The reaction mechanism and effects of the present invention are as follows:
[0010] 1. Carbonaceous materials are crucial in controlling the melting process of mold slag. They should have good heat preservation properties to prevent the mold slag from forming a hard shell or becoming too viscous in the crystallizer; at the same time, they can effectively control the melting speed to ensure the continuous supply of liquid slag. Among them, carbon black is the most commonly used carbonaceous material. However, excessive carbon black is also the culprit for the carbonization effect on molten steel.
[0011] The present invention firstly adsorbs polyethylene glycol on the surface of carbon black by ball milling, thereby increasing steric hindrance and weakening agglomeration tendency, so that the carbon black is evenly dispersed and has good stability. Then, a modifier is used for ultrasonic treatment again, and the surface groups of carbon black undergo physical adsorption and chemical grafting reactions successively. Finally, ultrasound is used to form a structure in which graphene oxide coats the modified carbon black. On the one hand, during the spray tower granulation process, high temperature usually thermally reduces graphene oxide to form graphene and / or graphite. Compared with the common method of directly adding graphite and carbon black, the carbonaceous material of the present invention combines the two well by physical and chemical means, thereby improving stability, thereby improving the overall performance of the carbonaceous material, and further making the crystallizer protective slag have a suitable melting rate and lubrication performance. On the other hand, different carbonaceous materials have different effects on the melting rate and melting structure of the protective slag. The present invention selects a specific ratio of carbon black and graphene oxide to form the carbonaceous material, so that the protective slag has a good thermal insulation effect and can have a suitable melting rate and viscosity.
[0012] 2. The binder can improve the adhesion between the mold slag and the wall of the crystallizer, prevent the mold slag from falling off prematurely, and ensure the formation of a continuous and uniform slag film throughout the continuous casting process. However, the dispersion performance of the commonly used binder starch will weaken at high temperatures.
[0013] After the binder of the present invention is modified by octenyl succinic anhydride, the number of hydroxyl groups in corn starch is reduced, and polyvinyl alcohol is further introduced, so that the modified binder has good film-forming and emulsifying properties, thereby making the surface of the protective slag smoother, which helps to improve the lubricity, wear resistance and stability of the protective slag. In addition, the modified binder can adjust the viscosity and fluidity so that it is evenly distributed in the crystallizer protective slag, while ensuring the continuity and uniformity of the slag film, thereby reducing the quality defects of the casting.
[0014] In some embodiments, the components of the mold slag are as follows: CaO: 30.10-37.27%, SiO 2 :31.49-38.22%, MgO: 3.86-6.19%, Fe 2 O 3 :≤1%,Al 2 O 3 :2.01-3.56%,Na 2 O: 1.32-3.02%, F - : 1.32-4.37%, B 2 O 3 : 0.84-1.94%, MnO: 0-1.10%, C: 5.37-9.74%, and the rest are other inevitable impurities.
[0015] In some embodiments, the method for preparing the carbonaceous material comprises the following steps:
[0016] S1. Mix carbon black and polyethylene glycol, and ball mill to obtain a material;
[0017] S2. The material obtained in step S1 is mixed with water, stirred, and then a modifier is added, ultrasonically treated, and dried to obtain a powder;
[0018] S3. Mix graphene oxide and water, add the powder obtained in step S2, perform ultrasonic treatment, and dry to obtain a carbonaceous material.
[0019] In some embodiments, the modifier in step S2 is a combination of N-β (aminoethyl) -γ-aminopropyltrimethoxysilane and sodium dodecyl sulfate.
[0020] Preferably, the mass ratio of N-β(aminoethyl)-γ-aminopropyltrimethoxysilane to sodium dodecyl sulfate is (2-3):1.
[0021] In some embodiments, the mass ratio of graphene oxide to powder in step S3 is 1:(9-15).
[0022] In some embodiments, the mass ratio of carbon black to polyethylene glycol in step S1 is 10:(0.1-0.2).
[0023] In some embodiments, the mass ratio of the material to the modifier in step S2 is 1:(0.025-0.05).
[0024] In some embodiments, the method for preparing the modified binder comprises the following steps:
[0025] Q1. Mix corn starch and water, heat to 90-95°C and stir, add octenyl succinic anhydride, stir and react to obtain a mixed solution;
[0026] Q2. To the mixed solution obtained in step Q1, an aqueous sodium hydroxide solution was added dropwise to adjust the pH to 8-8.5, heated to 35-50 ° C, stirred for 40-60 min, and then an aqueous hydrochloric acid solution was added dropwise to adjust the pH to 6.8-7.2 to obtain a liquid;
[0027] Q3. Mix the liquid obtained in step Q2 and a 10-20 wt% aqueous solution of polyvinyl alcohol, stir and heat to 60-80°C, react for 2-3 hours, adjust the pH to 6-8 with an aqueous solution of sodium hydroxide to obtain a modified binder.
[0028] In some embodiments, the mass ratio of corn starch to octenylsuccinic anhydride in step Q1 is (1.3-1.7):1.
[0029] In some embodiments, the mass ratio of corn starch to polyvinyl alcohol aqueous solution in the liquid in step Q3 is (12-18):1.
[0030] In some embodiments, the mold protection slag further comprises 0.4-1.0 parts by weight of sodium lignin sulfonate.
[0031] In some embodiments, the melting point of the mold slag is 1050-1100°C, and the viscosity at 1300°C is 0.25-0.4 Pa.s.
[0032] Another aspect of the present invention provides a method for preparing mold slag for medium carbon steel, comprising the following steps:
[0033] 1. Mix wollastonite, magnesium slag, quartz, bentonite, coke gemstone, fluorite, soda ash, manganese carbonate, boron glass powder and magnesia powder, melt, water quench, dry, crush and sieve to obtain pre-melted material;
[0034] 2. The premelt obtained in step 1, the carbonaceous material and the modified binder are mixed and stirred, and are successively put into a ball mill for dry grinding, a water mill for fine grinding and slurry making, and spray granulation to obtain a crystallizer protective slag.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The crystallizer protection slag of the present invention has a reasonable ratio of chemical components, suitable melting speed and viscosity, effectively ensures the thickness of the liquid slag layer, and enables the protection slag to be consumed evenly, thereby ensuring the smooth progress of the continuous casting process and avoiding quality defects such as corner cracks, narrow edge bulging, and transverse cracks at the corners of the medium carbon steel ingot.
[0037] 2. The carbonaceous material of the present invention is evenly dispersed and has good stability, which further enables the mold protection slag to have a suitable melting speed and lubricity. In addition, by selecting a specific ratio of carbon black and graphene oxide to form the carbonaceous material, the protection slag can have a suitable melting speed and viscosity while having a good heat preservation effect.
[0038] 3. The modified binder of the present invention has good film-forming and emulsifying properties, which helps to improve the lubricity, wear resistance and stability of the protective slag; at the same time, the modified binder can adjust the viscosity and fluidity of the protective slag and reduce the quality defects of the ingot. DETAILED DESCRIPTION
[0039] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, rather than to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0040] According to the ratios of the raw materials and the preparation methods specified in the following examples and comparative examples, each crystallizer protection slag is prepared.
[0041] In order to facilitate those skilled in the art to implement the present invention, some raw material manufacturers of the embodiments and comparative examples are described as follows:
[0042] Carbon black: purchased from Guangdong Dingxin Polymer Technology Co., Ltd., model 400R;
[0043] Polyethylene glycol: purchased from Hai'an Petrochemical Plant, Jiangsu Province, model PEG-1000;
[0044] Polyvinyl alcohol: purchased from Anhui Longyang Environmental Protection Technology Co., Ltd., model 26-99L2488;
[0045] Other raw materials are not specially specified and can be purchased from the market.
[0046] Preparation Example 1
[0047] The preparation method of carbonaceous material A comprises the following steps:
[0048] S1. Mix 100g carbon black and 15g polyethylene glycol and ball mill for 60min to obtain a material;
[0049] S2. 94 g of the material obtained in step S1 and 100 mL of water were mixed and stirred for 1 h, and then 2.5 g of N-β (aminoethyl) -γ-aminopropyltrimethoxysilane and 1 g of sodium dodecyl sulfate were added, ultrasonically treated for 30 min, and dried at 80 ° C for 4 h to obtain a powder;
[0050] S3. Mix 7 g of graphene oxide and 100 mL of water, add 84 g of the powder obtained in step S2, ultrasonically treat for 20 min, and dry at 90° C. to constant weight to obtain carbonaceous material A.
[0051] Preparation Example 2
[0052] The preparation method of carbonaceous material B is the same as that of Preparation Example 1, except that in step S2, 3.5 g of sodium dodecyl sulfate is used to replace the sum of 2.5 g of N-β (aminoethyl) -γ-aminopropyltrimethoxysilane and 1 g of sodium dodecyl sulfate.
[0053] Preparation Example 3
[0054] The preparation method of carbonaceous material C is the same as that of Preparation Example 1, except that the amount of graphene oxide added in step S3 is 5.5 g.
[0055] Preparation Example 4
[0056] The preparation method of the modified binder A comprises the following steps:
[0057] Q1. Mix 30g corn starch and 250mL water, heat to 90°C, stir at 500r / min for 45min, add 20g octenyl succinic anhydride, stir at 400r / min for 60min to obtain a mixed solution;
[0058] Q2. To the mixed solution obtained in step Q1, 0.02 mol / L aqueous sodium hydroxide solution was added dropwise to adjust the pH to 8.5, heated to 45 ° C, stirred for 50 min, and then 0.02 mol / L aqueous hydrochloric acid solution was added dropwise to adjust the pH to 7 to obtain a liquid;
[0059] Q3. Mix the liquid obtained in step Q2 and 2 g of a 15 wt% aqueous solution of polyvinyl alcohol, stir and heat to 70°C, keep warm for 2.5 hours, adjust the pH to 7 with a 0.02 mol / L aqueous solution of sodium hydroxide to obtain a modified binder A.
[0060] Preparation Example 5
[0061] The preparation method of modified binder B is the same as that of Preparation Example 4, except that the amount of octenyl succinic anhydride added in step Q1 is 15.8 g.
[0062] Preparation Example 6
[0063] The preparation method of modified binder C is the same as that of Preparation Example 4, except that the amount of polyvinyl alcohol aqueous solution added in step Q3 is 1.62 g.
[0064] Example 1
[0065] A mold protection slag for medium carbon steel, comprising the following raw materials by weight: 30 parts of wollastonite, 30 parts of magnesium slag, 4 parts of quartz, 3 parts of bentonite, 4 parts of coke gemstone, 6.5 parts of fluorite, 2 parts of soda ash, 1.5 parts of manganese carbonate, 5 parts of borosilicate glass powder, 3 parts of magnesia powder, 8 parts of carbonaceous material A, and 2.25 parts of modified binder A;
[0066] The method for preparing the mold powder of this embodiment comprises the following steps:
[0067] 1. Mix wollastonite, magnesium slag, quartz, bentonite, coke gemstone, fluorite, soda ash, manganese carbonate, boron glass powder and magnesia powder, melt at 1100°C, quench with water, dry at 500°C for 24h, and crush through a 200-mesh sieve to obtain a pre-melted material;
[0068] 2. The premelt obtained in step 1, carbonaceous material A and modified binder A are mixed and stirred for 3 hours, and then put into a ball mill for dry grinding, a water mill for fine grinding and slurry making, and spray granulation to obtain a crystallizer protective slag.
[0069] Example 2
[0070] A crystallizer protective slag for medium carbon steel, which comprises the following raw materials in parts by weight: 20 parts of wollastonite, 20 parts of magnesium slag, 2 parts of quartz, 1 part of bentonite, 2 parts of coke gemstone, 3 parts of fluorite, 1 part of soda ash, 1 part of manganese carbonate, 3 parts of borosilicate glass powder, 2 parts of magnesia powder, 6 parts of carbonaceous material A, and 1.5 parts of modified binder A.
[0071] The preparation method of the crystallizer protection slag in this embodiment is the same as that in Example 1.
[0072] Example 3
[0073] A crystallizer protection slag for medium carbon steel, which comprises the following raw materials in parts by weight: 40 parts of wollastonite, 40 parts of magnesium slag, 6 parts of quartz, 5 parts of bentonite, 6 parts of coke gemstone, 10 parts of fluorite, 3 parts of soda ash, 2 parts of manganese carbonate, 7 parts of borosilicate glass powder, 4 parts of magnesia powder, 10 parts of carbonaceous material A, and 3 parts of modified binder A.
[0074] The preparation method of the crystallizer protection slag in this embodiment is the same as that in Example 1.
[0075] Example 4
[0076] A crystallizer protection slag for medium carbon steel, which comprises the following raw materials in parts by weight: 30 parts of wollastonite, 30 parts of magnesium slag, 4 parts of quartz, 3 parts of bentonite, 4 parts of coke gemstone, 6.5 parts of fluorite, 2 parts of soda ash, 1.5 parts of manganese carbonate, 5 parts of borosilicate glass powder, 3 parts of magnesia powder, 8 parts of carbonaceous material A, 2.25 parts of modified binder A, and 0.7 parts of sodium lignin sulfonate.
[0077] The method for preparing the mold powder of this embodiment comprises the following steps:
[0078] 1. Mix wollastonite, magnesium slag, quartz, bentonite, coke gemstone, fluorite, soda ash, manganese carbonate, boron glass powder and magnesia powder, melt at 1100°C, quench with water, dry at 500°C for 24h, and crush through a 200-mesh sieve to obtain a pre-melted material;
[0079] 2. The premelt obtained in step 1, carbonaceous material A, modified adhesive A and sodium lignin sulfonate are mixed and stirred for 3 hours, and then put into a ball mill for dry grinding, a water mill for fine grinding and slurry making, and spray granulation to obtain a crystallizer protective slag.
[0080] Example 5
[0081] A mold protection slag for medium carbon steel and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal amount of carbonaceous material B is used to replace carbonaceous material A.
[0082] Example 6
[0083] A mold protection slag for medium carbon steel and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 2, except that an equal amount of carbonaceous material C is used to replace carbonaceous material A.
[0084] Example 7
[0085] A mold protection slag for medium carbon steel and a preparation method thereof, wherein the specific implementation method is the same as that of Example 2, except that an equal amount of commercially available carbon black is used to replace carbonaceous material A.
[0086] Example 8
[0087] A mold protection slag for medium carbon steel and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 2, except that an equal amount of modified binder B is used to replace modified binder A.
[0088] Example 9
[0089] A mold protection slag for medium carbon steel and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 2, except that an equal amount of modified binder C is used to replace modified binder A.
[0090] Comparative Example 1
[0091] A mold protection slag for medium carbon steel and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal amount of commercially available corn starch is used to replace the modified binder A.
[0092] Effect evaluation:
[0093] The mold protection slag obtained in the above-mentioned Examples 1-9 and Comparative Example 1 was tested and analyzed, and the specific results are shown in Table 1.
[0094] Performance Test:
[0095] (1) Viscosity test: refer to test standard YB / T185-2017;
[0096] (2) Surface quality defect test: The obtained mold protection slag is used in the production of medium carbon steel in the steel plant, and the ratio of the surface quality defect area to the total area is calculated.
[0097] Table 1
[0098] Serial number The viscosity at 1300℃ is / Pa.s Surface quality defects / % Example 1 0.35 0.18 Example 2 0.38 0.30 Example 3 0.37 0.24 Example 4 0.34 0.15 Example 5 0.23 0.36 Example 6 0.22 0.40 Example 7 0.20 0.49 Example 8 0.22 0.36 Example 9 0.20 0.42 Comparative Example 1 0.17 0.47
[0099] From the results in Table 1, it can be seen that the mold protection slag prepared in Examples 1-4 has an appropriate viscosity and very few surface quality defects.
[0100] Compared with Example 1, when preparing carbonaceous materials, Example 5 changes the type of modifier, and Example 6 changes the mass ratio of graphene oxide and powder, which reduces stability, affects viscosity, and increases surface quality defects. Example 7 replaces carbonaceous materials with carbon black, which results in uneven dispersion, and thus fails to improve the thermal insulation of the carbonaceous materials. In addition, the viscosity exceeds the appropriate range, thereby increasing surface quality defects.
[0101] Compared with Example 1, when preparing the modified adhesive, Example 8 changes the mass ratio of corn starch and octenylsuccinic anhydride, and Example 9 changes the mass ratio of corn starch and polyvinyl alcohol aqueous solution in the liquid, which reduces the heat resistance and reduces the adhesion of the adhesive, thereby increasing the surface quality defects; Comparative Example 1 uses commercially available corn starch to replace the modified adhesive, which reduces the thermal stability and adhesion of the adhesive, thereby increasing the surface quality defects.
[0102] The above is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present application. Although the present application is disclosed as above in the preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution.
Claims
1. A mold protection slag for medium carbon steel, characterized in that: The crystallizer protective slag comprises the following raw materials by weight: 20-40 parts of wollastonite, 20-40 parts of magnesium slag, 2-6 parts of quartz, 1-5 parts of bentonite, 2-6 parts of pyroxene, 3-10 parts of fluorite, 1-3 parts of soda ash, 1-2 parts of manganese carbonate, 3-7 parts of borosilicate glass powder, 2-4 parts of magnesia powder, 6-10 parts of carbonaceous material, and 2-4 parts of modified binder.
2. The mold protection slag for medium carbon steel according to claim 1, characterized in that: The components of the protective slag are as follows: CaO: 30.10-37.27%, SiO2: 31.49-38.22%, MgO: 3.86-6.19%, Fe2O3: ≤1%, Al2O3: 2.01-3.56%, Na2O: 1.32-3.02%, F - : 1.32-4.37%, B2O3: 0.84-1.94%, MnO: 0-1.10%, C: 5.37-9.74%, and the rest are other inevitable impurities.
3. The mold protection slag for medium carbon steel according to claim 1, characterized in that: The method for preparing the carbonaceous material comprises the following steps: S1. Mix carbon black and polyethylene glycol, and ball mill to obtain a material; S2. The material obtained in step S1 is mixed with water, stirred, and then a modifier is added, ultrasonically treated, and dried to obtain a powder; S3. Mix graphene oxide and water, add the powder obtained in step S2, perform ultrasonic treatment, and dry to obtain a carbonaceous material.
4. The mold protection slag for medium carbon steel according to claim 3, characterized in that: The modifier in step S2 is a composition of N-β (aminoethyl) -γ-aminopropyltrimethoxysilane and sodium dodecyl sulfate.
5. The mold protection slag for medium carbon steel according to claim 3, characterized in that: The mass ratio of graphene oxide to powder in step S3 is 1:(9-15).
6. The mold powder for medium carbon steel according to claim 1, characterized in that: The preparation method of the modified binder comprises the following steps: Q1. Mix corn starch and water, heat to 90-95°C and stir, add octenyl succinic anhydride, stir and react to obtain a mixed solution; Q2. To the mixed solution obtained in step Q1, an aqueous sodium hydroxide solution was added dropwise to adjust the pH to 8-8.5, heated to 35-50 ° C, stirred for 40-60 min, and then an aqueous hydrochloric acid solution was added dropwise to adjust the pH to 6.8-7.2 to obtain a liquid; Q3. Mix the liquid obtained in step Q2 and a 10-20 wt% aqueous solution of polyvinyl alcohol, stir and heat to 60-80°C, react for 2-3 hours, adjust the pH to 6-8 with an aqueous solution of sodium hydroxide to obtain a modified binder.
7. The mold powder for medium carbon steel according to claim 6, characterized in that: The mass ratio of corn starch to octenylsuccinic anhydride in step Q1 is (1.3-1.7):
1.
8. The mold powder for medium carbon steel according to claim 6, characterized in that: The mass ratio of corn starch to polyvinyl alcohol aqueous solution in the liquid in step Q3 is (12-18):
1.
9. The mold powder for medium carbon steel according to claim 1, characterized in that: The melting point of the protective slag is 1050-1100°C, and the viscosity at 1300°C is 0.25-0.4 Pa.s.
10. A method for preparing a mold protection slag for sealing electric vacuum devices according to any one of claims 1 to 9, characterized in that: The following steps are included:
1. Mix wollastonite, magnesium slag, quartz, bentonite, coke gemstone, fluorite, soda ash, manganese carbonate, boron glass powder and magnesia powder, melt, water quench, dry, crush and sieve to obtain pre-melted material; 2. The premelt obtained in step 1, the carbonaceous material and the modified binder are mixed and stirred, and are successively put into a ball mill for dry grinding, a water mill for fine grinding and slurry making, and spray granulation to obtain a crystallizer protective slag.
Citation Information
Patent Citations
Crystallizer casting powder for casting high-hydrogen-content medium carbon steel molten steel and application of crystallizer casting powder
CN116274906A
Cited By
A protective slag for producing silicon-manganese spring steel and a preparation method thereof
CN119733809A
Special casting powder for oriented silicon steel for high-speed rail traction motor
CN120587415A